8 - ABDALLA BUJRA: A Life of Unparalleled Service - Adebayo O. Olukoshi, (CODESRIA Bulletin, 2025)
It was late 2023 when, after several weeks of consultation among colleagues in Dakar, Nairobi, Addis Ababa and Johannesburg, a group of us decided to pay a visit to the second Executive Secretary of CODESRIA, Professor Abdalla Bujra, in his retirement home in Malindi, Kenya. It is difficult to say exactly what it was that brought about the meeting of minds across the continent, that a visit to him was not only long overdue but had become an urgent imperative. My guess, though, is that among us – mentees, younger colleagues, friends and admirers – there was a shared feeling that, several years after his retirement, there was a very good case for going to Malindi to spend a day with him and reminiscing about the times we had spent together under his guidance and leadership. I am glad the trip to Malindi took place, and I am grateful to have been part of the mission. As it would turn out, it was the last time we would see him.